Tinjauan Hukum Kesepakatan Suami Istri Diluar Ketentuan Mengenai Pemisahan Harta dalam Perjanjian Perkawinan - Salsabilla, Denintya Indri; Endah Hartati (UNES Law Review, 2024)
This study examines the regulations regarding a prenuptial agreement which contain agreements between husband and wife outside of provisions regarding the separation of assets. In marriage, apart from assets, there are also other personal matters that can be agreed upon, but the legal provisions only stipulate that a prenuptial agreement specifically concern about separation of assets. This study uses research methods with a qualitative approach and in its discussion uses a juridical-normative approach. The results of this study found that husband and wife agreements outside of assets can be made if necessary but are considered difficult to include in a prenuptial agreement. This is because there are several differences, so the way it made must also be differentiated.